1999
DOI: 10.1002/(sici)1098-2396(199911)34:2<145::aid-syn7>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 5-HT1A receptor ligands on Fos-like immunoreactivity in rat brain: Evidence for activation of noradrenergic transmission

Abstract: This study investigated the effects of 8-OH-DPAT and various other 5-HT(1A) receptor agonists on brain noradrenergic transmission using Fos-like immunoreactivity (Fos-LI) as a marker of neural activation. Administration of 8-OH-DPAT (0.1 and 1 mg/kg) induced a marked and dose-related increase in the number of cells positive for Fos-LI in the locus coeruleus (LC), the main source of noradrenergic projections to the forebrain. This effect was also induced by the non-selective, partial 5-HT(1A) receptor agonist b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
5
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 30 publications
3
5
0
Order By: Relevance
“…Conversely, antagonism of cell body autoreceptors by the 5‐HT 1A receptor antagonist WAY 100 635 indirectly decreases the firing rate of locus coeruleus neurons via stimulation of postsynaptic 5‐HT 2A receptors (Szabo & Blier, 2001). These findings are consistent with the reported enhancement of c‐ fos immunoreactivity within the locus coeruleus by the 5‐HT 1A receptor agonist 8‐OH‐DPAT (Hajos‐Korcsok & Sharp, 1999). Stimulation of 5‐HT 1B terminal autoreceptors would also be expected to decrease serotonergic inhibition of the locus coeruleus and lead to an increase in c‐ fos immunoreactivity in these cells.…”
Section: Discussionsupporting
confidence: 91%
“…Conversely, antagonism of cell body autoreceptors by the 5‐HT 1A receptor antagonist WAY 100 635 indirectly decreases the firing rate of locus coeruleus neurons via stimulation of postsynaptic 5‐HT 2A receptors (Szabo & Blier, 2001). These findings are consistent with the reported enhancement of c‐ fos immunoreactivity within the locus coeruleus by the 5‐HT 1A receptor agonist 8‐OH‐DPAT (Hajos‐Korcsok & Sharp, 1999). Stimulation of 5‐HT 1B terminal autoreceptors would also be expected to decrease serotonergic inhibition of the locus coeruleus and lead to an increase in c‐ fos immunoreactivity in these cells.…”
Section: Discussionsupporting
confidence: 91%
“…Increased monoaminergic transmission is a candidate mechanism as Arc and c-fos expression in parietal cortex is activated by noradrenaline and 5-HT (eg. Hajós-Korcsok and Sharp, 1999;Pei et al, 2000). Thus, GR 205,171 causes a stereospecific increase both in the electrical activity of ascending noradrenergic neurones and in the release of cortical noradrenaline at a dose corresponding to that active in the present study (Millan et al, 2001).…”
Section: Discussionsupporting
confidence: 55%
“…Although the contribution of 5-HT in the OFC to the emotional behavior such as anxiety- and depression-like behavior is less understood in rodents, it is reported that microinjection of 5-HT 1A or 5-HT 1B receptors agonist into the OFC suppressed aggressive behavior in mice (De Almeida et al, 2006; Centenaro et al, 2008; Stein et al, 2013). Also, systemic administration of 5-HT 1A receptor agonist or 5-HT reuptake inhibitor enhanced the firing of principal neurons and the expression of c-fos in the PFC (Hajós-Korcsok and Sharp, 1999; Jongsma et al, 2002; Lladó-Pelfort et al, 2012). Therefore, 5-HT may regulate affective behaviors via modulation of intrinsic neural activity in the OFC in addition to mediating the information from the OFC.…”
Section: Discussionmentioning
confidence: 99%